Hubungan Pijat Oksitosin Dengan Pengeluaran Asi Pada Ibu Post Partum Di RS Ibu Kartini Kisaran Kecamatan Kisaran Barat Kabupaten Asahan Tahun 2022 - Reni Sandriani; Parningotan Simanjuntak; Ingka Kristina Pangaribuan; Astaria Br Ginting (Jurnal Siti Rufaidah, 2024)
Breast preparation for breastfeeding begins during pregnancy, which is characterized by the breasts becoming larger along with the increase in the number and size of the alveoli glands as a result of increasing levels of the hormone estrogen. This occurs until a baby has been breastfed for a few days when actual milk production begins. In the first few days the breasts secrete colostrum which is very important for the baby's health. Breasts produce breast milk starting when the baby begins to suckle on the nipple and the resulting physical stimulation causes impulses in the nerve endings which are then sent to the hypothalamus in the brain which in turn tells the pituitary gland in the brain to produce the hormones oxytocin and prolactin (Anik, 2016). This study aims to analyze the relationship between oxytocin massage and breast milk production in postpartum mothers at Ibu Kartini Hospital, West Kisaran, Asahan Regency in 2023. This research is correlational with a cross sectional approach and bivariate data analysis is data analysis used in research to determine the relationship or influence of variables. independent (independent) with a dependent (dependent) variable using Chi Square analysis with a significant p-value (0.05) (Hardani, 2020) Based on the research results. Based on the results of statistical tests using Chi-Square, it was obtained with a p value of 0.001 that the breast milk output of postpartum mothers before oxytocin massage was mostly not enough breast milk. Postpartum mothers' breast milk output after massage is mostly breast milk This means that there is an influence of oxytocin massage on breast milk production in postpartum mothers at Ibu Kartini Hospital, West Kisaran, Asahan Regency in 2023